HUBUNGAN ASUPAN JENIS BERAS TERHADAP KADAR GLUKOSA DARAH SEWAKTU PADA PASIEN DIABETES MELLITUS TIPE II - Utami Dewi, Ayu Dian; Sutadarma, I Wayan Gede; Wiryanthini, Ida Ayu Dewi (E-Jurnal Medika Udayana; Vol 11 No 5 (2022): E-Jurnal Medika Udayana, 2022)
Type II DM is a metabolic disease characterized by increase blood glucose level is caused secretion insulin dysfunction and insulin resistance. An increase in the incidence of DM can occur because of an unbalanced diet. Aim this study to determine the relationship of rice type intake with random blood glucose levels in type II DM patients. This study was a cross sectional analytic study which was conducted from September until November 2020 at the Puskesmas Denpasar Barat I and II. The sample in this study were patients with type II DM who met the inclusion criteria is a patient with a consuming rice, and a patient without using insulin. Exclusion criteria were a patient without consuming rice. Samples were obtained using simple random sampling technique and obtained 31 samples that met the inclusion criteria. The study was conducted by asking the sample for informed consent and asking sample to fill out an online questionnaire that contain food intake that the sample consumes in a day. Normality test is using Saphiro-wilk test and bivariate analysis with Rank-Spearman test. White rice type intake was 61,3%, red rice type intake was 35,5% and black rice type was 3,2%. Carbohydrate of rice intake in women amounted to 95,281 grams and in men 101, 810 grams. Calorie intake per day for women was 1226,0 kcal and in men was 1300,6 kcal. From analysis result there is a relationship between rice type intake, calorie, and carbohydrate with random blood glucose level (p= 0,000, p= 0,000, p= 0,000). Strength of correlation (r= 0,717, r= 0,945, r= 0,945). There is a significant relationship between rice type intake on random blood glucose level with a strong correlation.